Effects of Thermal Processing on Fatty Acids Profile of Wild Sea Bream (Sparus Aurata) from Latakia Coast - الحاج علي أنور; ياسين مفيد; عاقل رهف (Latakia University Journal -Medical Sciences Series, 2021)
The effects of thermal processing (deep frying in Sunflower oil, grilling, roasting) on the fatty acids profile especially Docosahexaenoic acid (DHA) and Eicosapentaenoic acid (EPA) of wild Sea Bream (Sparus Aurata) from Latakia coast, were studied using Gas Chromatography Technique (GC). Analysis was performed at laboratories of faculty of Agricultural Engineering at Damascus University and faculty of Pharmacy at Tishreen University from 2019 to 2020. Moisture and total fat content on the base of dry matter were determined in all sample treatments. The results revealed significant differences in both EPA and DHA fatty acid values between heat treatment methods . The average of EPA and DHA estimated by g/100g of fatty acids methyl esters (FAMEs) in control samples were 2.71 and 11.23, respectively. Frying revealed a remarkable decrease in these two fatty acids values, as they were 1.1 and 1.38 g/100g of FAMEs, respectively, while it was accompanied by a significant increase in the percentage of C18:2n-6 fatty acid, reaching 52.76 compared with 3.02 g/100g of FAMEs for the control samples, this remarkable increase was attributed to the absorption of sunflower oil by the samples during frying. However, the percentages of EPA and DHA in grilling were 5.32 and 3.85 g/100g of FAMEs respectively, with a significant decrease in the percentage of DHA compared with the control samples. No significant differences were noticed in DHA percentage between control and roasted samples at the same time roasting kept the highest levels of EPA and DHA with average of 6.77 and 10.5 g/ 100g of fatty acids methyl esters, respectively. As a result it was the best among all applied heat treatment.